Bigger calves make better cows. Fact or fantasy in variable environments? - Coppock, D. Layne (1989)
Examines the growth performance up to 3 years of calves raised under different treatments including calves with a background of simulated pastoral management and received half of their dams milk, calves received supplements of medium quality lucerne hay, calves given water as nightly supplement, and two control groups with one receiving no supplementary feed or water and the other receiving no supplements and managed traditionally under semi-arid conditions in Ethiopia.